2017
DOI: 10.1177/1010428317704805
|View full text |Cite
|
Sign up to set email alerts
|

siRNA-mediated silencing of bFGF gene inhibits the proliferation, migration, and invasion of human pituitary adenoma cells

Abstract: Human pituitary adenoma is one of the most common intracranial tumors with an incidence as high as 16.7%. Recent evidence has hinted a relationship between growth factors of pituitary or hypothalamic origin and proliferation of human pituitary adenoma cells. This study explores the effects of small interfering RNA-mediated silencing of basic fibroblast growth factor gene on the proliferation, migration, and invasion of human pituitary adenoma cells. Human pituitary adenoma tissues were collected to obtain huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
(38 reference statements)
1
6
0
Order By: Relevance
“…Interestingly, Almong et al described endocan was markedly expressed in concordance with the switch between dormant to fast growing phenotype in experimental angiogenic tumors (15). Moreover, the enhanced FGF2 expression we found in ESM1 positive tumors could be supporting the fast-growing state in these tumors as FGF2 has been linked to invasion in cancer and in pituitary adenomas as well (35,43).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Interestingly, Almong et al described endocan was markedly expressed in concordance with the switch between dormant to fast growing phenotype in experimental angiogenic tumors (15). Moreover, the enhanced FGF2 expression we found in ESM1 positive tumors could be supporting the fast-growing state in these tumors as FGF2 has been linked to invasion in cancer and in pituitary adenomas as well (35,43).…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, the knockdown of Esm1 in HUVEC endothelial cells inhibited tube formation and increased sensitivity to the anti-angiogenic Avastin treatment in vitro, indicating endocan could be a molecular target for pituitary adenoma treatment (34). Additionally, in human pituitary adenoma cells in vitro, silencing FGF2 inhibited cell proliferation and invasion capacity (35).…”
Section: Discussionmentioning
confidence: 99%
“…From the invasive PitNET-related lncRNA expression dataset GSE51618, lncRNA XIST with high expression at a large FC in invasive PitNET was exhibited as the candidate lncRNAs (Figure 1A). In addition, a prior study revealed that siRNA-mediated bFGF gene silencing has the potential to inhibit the proliferation, migration and invasion of human PitNET cells 20. However, it is not clear whether XIST is involved in the regulation of bFGF in invasive PitNET.…”
Section: Resultsmentioning
confidence: 99%
“…The cells in each group were homogenized using a homogenizer (POLYTRON PT2100; Kinematic, Luzern, Switzerland) with ice-cold lysis buffer containing 1 mM phenylmethylsulfonyl fluoride to extract total protein. The proteins were separated on 10% SDS-PAGE 26 and transferred to nitrocellulose membrane. After being blocked, the transferred proteins were incubated with relevant antibodies against OGFr (1:1,000; Sigma), Bax, BCL-2, caspase-3, PARP, β-actin (all above 1:1,000; Cell Signaling Technology, Danvers, MA, USA) overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%